1987
DOI: 10.1159/000288045
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and Death in Anorexia nervosa

Abstract: Several deaths in patients with anorexia nervosa have been ascribed to ‘inanition’. The proximate cause of death from inanition has not been established. There are few previous reports of life-threatening hypoglycemia in anorexia nervosa. We participated in the care of two severely cachectic women with anorexia nervosa who were in coma with serum glucose levels of 8 and 14 mg/dl, respectively. Both patients became alert after administration of intravenous glucose. Both were found to have pneumonia at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…In addition, cases were also commonly dehydrated and had high rates of comorbid psychiatric illness and poor physical condition including anemia, osteoporosis, metabolic derangements, substance use, and depression. These observations are consistent with reports in the clinical literature of increased morbidity associated with infection (Copeland & Herzog, 1987;Devuyst et al, 1993). However, infection cases did not have lower BMI, longer hospitalizations, longer times since AN diagnosis, nor more previous hospital admissions than AN noncases, suggesting that infection cases were not obviously more debilitated than AN noncases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, cases were also commonly dehydrated and had high rates of comorbid psychiatric illness and poor physical condition including anemia, osteoporosis, metabolic derangements, substance use, and depression. These observations are consistent with reports in the clinical literature of increased morbidity associated with infection (Copeland & Herzog, 1987;Devuyst et al, 1993). However, infection cases did not have lower BMI, longer hospitalizations, longer times since AN diagnosis, nor more previous hospital admissions than AN noncases, suggesting that infection cases were not obviously more debilitated than AN noncases.…”
Section: Discussionsupporting
confidence: 92%
“…However, little is known about the relationship between these and other clinical variables (e.g., leukocyte count), although AN patients with infection are reported to have an increased rate of infectious complications (Copeland & Herzog, 1987;Devuyst et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Asymptomatic hypoglycemia is common among AN patients and is noteworthy because of its relationship to sudden death (Copeland & Herzog, 1987). Studies of patients with diabetes mellitus or short-term starvation have revealed that some patients who experienced a hypoglycemic state demonstrated decreased threshold values for stimulation of secretion of insulin-counterregulatory hormones and displayed asymptomatic hypoglycemia (Amiel, Sherwin, Simonson, & Tamborlane, 1988;Heller & Cryer, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Reactive hypoglycemia is of particular importance in AN patients because of its relationship to the life-threatening events (Copeland & Herzog, 1987). However, the relationship among reactive hypoglycemia, corresponding insulin metabolism, and eating behavior has not been well documented.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically signi®cant hypoglycaemia causes sweating, tremor, drowsiness, irritability, faints, profound bradycardia (slow heart rate) (Pollock et al, 1996), coma and death. Concurrent infection (Copeland and Herzog, 1987), alcohol misuse and excessive exercise (Smith, 1988) signi®cantly increase the risk of hypoglycaemic coma.…”
Section: Glucosementioning
confidence: 99%